PRODUKTIVITAS DAN BIAYA PENGELUARAN LIMBAH PEMANENAN KAYU PADA HUTAN ALAM PEGUNUNGAN: STUDI KASUS DI PT. JATI DHARMA INDAH PLYWOOD INDUSTRIES KABUPATEN NABIRE, PAPUA - Soenarno; Dulsalam; Yuniawati (BRIN Publishing, 2020)
At present, logging activities have implemented Reduced Impact Logging (RIL) technology, but logging waste stilloccurs on average 17%. The logging waste has not been utilized because of the alleged high cost of production due toimproper wood harvesting method. This study aims to obtain data and information on productivity and skidding costsof wood harvesting waste in mountainous natural forest areas. The results showed that the cost of producing woodharvesting waste with the tree-length logging method at ± 2 hm skid distance was Rp 35,693/m3, but when usingthe conventional method is Rp 349,125/m3. The tree-length logging method can not only remove the main wood butalso free from branched wood waste (BBC) and trunk above the branch (BAC) till to landing site but also but it canincrease the efficiency of wood utilization. However, the application of the tree-length logging method resulted in adecrease in logging productivity of 16.47% and skidding of 14.41% at an average skid distance of 3 hm. The averageproductivity of logging in the conventional method is 62.514 m3/hour while the tree length logging method is 52.289m3/hour. The average productivity of skidding tree-length logging method is 17.301 m3/hour but the conventionalmethod is 18.249 m3/hour. For the tree length logging method to be implemented in the field, it is necessary to makechanges in the tariffs for felling and skidding wages following the reduced level of work productivity.